2006
DOI: 10.1007/s11365-006-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Guest editorial: Female and ethnic minority entrepreneurship

Abstract: There has been an increasing level of interest in diversity in small business enterprises. This diversity has been largely focused on female and ethnic minority entrepreneurs. Although there is evidence that female entrepreneurship can have a positive impact on economic prosperity, levels of earnings remain low. The articles in this special issue further our understanding of female and minority entrepreneurs. They examine important topics such as the differences between male and female entrepreneurs in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
2
30
1
1
Order By: Relevance
“…Previous commentators and evidence have suggested that one of the areas in which female entrepreneurs may outshine men is in their abilities to build strong inter-personal relationships (Birley et al, 1987;Daniel, 2004;Fuller-Love et al, 2006), so perhaps it is not surprising that these two additional clusters emerge in this study.…”
Section: Competencies Of Women Entrepreneursmentioning
confidence: 57%
“…Previous commentators and evidence have suggested that one of the areas in which female entrepreneurs may outshine men is in their abilities to build strong inter-personal relationships (Birley et al, 1987;Daniel, 2004;Fuller-Love et al, 2006), so perhaps it is not surprising that these two additional clusters emerge in this study.…”
Section: Competencies Of Women Entrepreneursmentioning
confidence: 57%
“…According to previous research, women face more problems than do men in raising venture capital or taking out bank loans (Greene, Brush, Hart, & Saparito, 2001;Brush, Carter, Gatewood, Greene, & Hart, 2004;Fuller-Love, Lim, & Akehurst, 2006). Some research does not exclude the impact of existing general perceptions on different gender-based behavioural patterns (Robb & Wolken, 2002;Huang & Kisgen, 2008) that might affect banks' attitudes towards women and men.…”
Section: Gendermentioning
confidence: 99%
“…Consequently a part of earlier studies (Sena et al, 2012;Watson et al, 2009) deals with the question of whether such gender gap is caused by women's greater problems with funding. A large number of previous studies (Brush et al, 2004;Fuller-Love et al, 2006;Muravyev et al, 2009), however, have confirmed that women face greater difficulties than men in receiving bank loans. Other studies (Klyver and Grant, 2010) point to factors such as women's weaker and less influential networks as reasons for their lower levels of willingness to start a business, while other researchers (Foss, 2010;Garcia and Carter, 2009) find no difference between female and male entrepreneurs in their networks.…”
Section: The Gender Perspective In Businessmentioning
confidence: 99%
“…Women have shown great interest in becoming entrepreneurs (Parker, 2010), but such constraints can negatively affect their motivation to start. A detailed business plan by an external advisor can provide a bank with a vision and strategy that can greatly increase a business proposal's chance of approval (Bruke et al, 2010); this is particularly true for women, who face higher rejection rates from banks than men (Brush et al, 2004;Fuller-Love et al, 2006).…”
mentioning
confidence: 99%